2015
DOI: 10.1007/s00520-015-3013-1
|View full text |Cite
|
Sign up to set email alerts
|

Mother-caregiver expectations for function among survivors of childhood brain tumors

Abstract: Purpose Children diagnosed with brain tumors increasingly survive to adulthood, although they do so with needs often requiring continued parental caregiving. We sought to describe the nature of caregivers’ expectations about survivors’ function and how expectations connect to ongoing management and decision-making. Methods Forty-five qualitative interviews with mother-caregivers were conducted and coded for themes related to expectations for their adolescent/young adult children living post-childhood brain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 37 publications
1
30
0
1
Order By: Relevance
“…In some cases, this threat stopped parents from planning future activities, and instead, they lived very much in the present . Another source of uncertainty came from whether their child would ever reach independence . In one study, the majority of parents believed their child would never be independent .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In some cases, this threat stopped parents from planning future activities, and instead, they lived very much in the present . Another source of uncertainty came from whether their child would ever reach independence . In one study, the majority of parents believed their child would never be independent .…”
Section: Resultsmentioning
confidence: 99%
“…Two articles highlighted that different caregivers and families deal with survivorship differently and will have different needs . One study found that clinicians find it challenging to tailor interventions to family and caregiver needs, as tools to assess family functioning and caregiver coping are not available .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mothers usually make countless decisions for their children, generally until the decision making at some point shifts to the (now older) healthy child. Mothers of children in cancer treatment or survivorship similarly make countless decisions, although shifting decision making may not follow prognostic recovery patterns for those with sufficient neurologic injury, and these decisions have been shown to be influenced by expectations for function, independence, and the future in general (Lucas, 2014). Indeed, recent work has focused on the powerful stories of parents’ experiences after the diagnosis of a childhood brain tumor, including struggles in survivorship related to treatment-related sequelae (Anonymous Three, 2014; Carlson, 2014; Rocker, 2014; Scheumann, 2014).…”
Section: Introductionmentioning
confidence: 99%